Klaus Wyrtki and the Modern Era of the Maritime Continent Oceanography - Gordon, Arnold (Marine Research in Indonesia, 2019)
The December 2019 issue of Marine Research in Indonesia on "Oceanography of the Indonesian Seas" is dedicated to Klaus Wyrtki. In many ways, Klaus Wyrtki's contribution to the study of the Indonesian seas served as a smooth transition from the era of the great expeditions such as the Dutch Willebrord Snellius Expedition (1929-1930; see Wüst, 1964; van Aken, 2005) of the early and mid-20th century to the modern era. In the NAGA Report (Wyrtki, 1961; also see Wyrtki, 2005), Klaus used existing ocean observations, supplemented with data he helped collect on the Indonesian research ship Samudera during his sojourn in Indonesia (1954-1957) as Head of the Institute of Marine Research in Jakarta to map out a broad view of the Southeast Asian waters (the waters of the Maritime Continent including the Indonesian seas). He presented the geography, the configuration of the seas and basins of the Southeast Asian waters, the surface circulation, and governing dynamics, including the tides and monsoonal driven seasonality, and the temperature/salinity surface layer patterns, as well as aspects of the subsurface stratification. The Plates 1-44 beautifully reveal the oceanographic condition of the Southeast Asian waters as resolved by the pre-1960 observations. As Klaus Wyrtki says in the NAGA Report Preface: "It is hoped that workers in the region, whether in oceanography or other branches of science may find it a source of information and a stimulus to undertake further research in these waters" and "The scientific publications dealing with this region show not so much a lack of observations as a lack of an adequate attempt to synthesize these results to give a comprehensive description of the region." "I soon decided to devote most of my time during my three years’ stay in Indonesia to the preparation of a general description of the oceanography of these waters." He succeeded.